Drought indicators revisited: the need for a wider consideration of environment and society. (11th May 2016) - Bachmair, Sophie; Stahl, Kerstin; Collins, Kevin; Hannaford, Jamie; Acreman, Mike; Svoboda, Mark; Knutson, Cody; Smith, Kelly Helm; Wall, Nicole; Fuchs, Brian; Crossman, Neville D.; Overton, Ian C.
Abstract : Drought indicators are proliferating, but with little consideration of which are most meaningful for describing drought impacts. A number of recent reviews compare different drought indicators, but none assess which indicators are actually used in the many operational drought monitoring and early warning efforts, why they were selected, or whether they have been 'ground‐truthed, ' i.e., compared with information representing local drought conditions and/or impacts. Also lacking is a comprehensive assessment of the state of monitoring drought impacts. To help fill this gap, we combine a review of drought indicators and impacts with a survey of 33 providers of operational drought monitoring and early warning systems from global to regional scales. Despite considerable variety in the indicators used operationally, certain patterns emerge. Both the literature review and the survey reveal that impact monitoring does exist but has rarely been systematized. Efforts to test drought indicators have mostly focused on agricultural drought. Our review points to a current trend towards the design and use of composite indicators, but with limited evaluation of the links between indicators and drought impacts. Overall, we find that much progress has been made both in research and practice on drought indicators, but monitoring and early warning systems are not yet strongly linked with the assessment of wider impacts on the environment and society. To understand drought impacts fully requires a better framing of drought as a coupled dynamic between the environment and society. WIREs Water 2016, 3:516–536. doi: 10.1002/wat2.1154 This article is categorized under: Engineering Water > Planning Water Science of Water > Methods Science of Water > Water Extremes